Origins of archaeal tetraether lipids in sediments: Insights from radiocarbon analysis RID A-6723-2009 - Shah, Sunita R.; Mollenhauer, Gesine; Ohkouchi, Naohiko; Eglinton, Timothy I.; Pearson, Ann (Geochimica et Cosmochimica Acta, 2008)
Understanding the supply and preservation of glycerol dibiphytanyl glycerol tetraethers (GDGTs) in marine sediments helps inform their use in paleoceanography. Compound-specific radiocarbon measurements of sedimentary alkenones from multiple environments have been used to gain insight into processes that affect U-37(K') paleotemperature reconstructions. Similar analyses are warranted to investigate how analogous processes affecting GDGTs impact TEX86 paleotemperatures. Here we present radiocarbon measurements on individual GDGTs from Bermuda Rise and Santa Monica Basin sediments and discuss the results in the context of previous studies of co-depositional alkenones and foraminifera. The C-14 contents of GDGTs and planktonic foraminifera in Bermuda Rise are very similar, suggesting a local source; and TEX86-derived temperatures agree more closely with foraminiferal temperatures than do U-37(K') temperatures. In contrast, GDGTs in Santa Monica Basin are depleted in C-14 relative to both alkenones and foraminifera, and TEX86 temperatures agree poorly with known surface water values. We propose three possible factors that could explain these results: (i) GDGTs may be labile relative to alkenones during advective transport through oxic waters; (ii) archaeal production deep in the water column may contribute C-14-depleted GDGTs to sediments; and (iii) some GDGTs also may derive from sedimentary archaeal communities. Each of these three processes is likely to occur with varying relative importance depending on geographic location. The latter two may help to explain why TEX86 temperature reconstructions from Santa Monica Basin do not appear to reflect actual sea surface temperatures. Terrigenous GDGTs are unlikely to be major contributors to Bermuda Rise or Santa Monica Basin sediments, based on values of the BIT index. The results also indicate that the crenarchaeol regioisomer is governed by processes different from other GDGTs. Individual measurements of the crenarchaeol regioisomer are significantly depleted in C-14 relative to co-occurring GDGTs, indicating an alternative origin for this compound that presently remains unknown. Re-examination of the contribution of crenarchaeol regioisomer to the TEX86 index shows that it is a significant influence on the sensitivity of temperature reconstructions. (C) 2008 Elsevier Ltd. All rights reserved.
id: 2051; PT: J; UT: WOS:000259107700010